PRACTICE OF REGULATING THE CRYPTO-ASSET MARKET IN THE DIGITAL ECONOMY (World Bulletin of Management and Law, 2026)
This article analyses the role of blockchain technologies and crypto assets in enabling decentralized and transparent management of financial transactions. The results of the analysis show that investor financial safety and protection are ensured through licensing of crypto-assets, implementation of AML and KYC systems via virtual asset service providers (VASPs), as well as pilot testing of experimental projects using the “regulatory sandbox” mechanism. The article emphasises the importance of temporary tax benefits and preferential fiscal mechanisms in the field of crypto assets to stimulate innovative companies and shape the digital financial ecosystem.